Das Rumäniendeutsche in der Neuauflage (2016) des Variantenwörterbuchs des Deutschen. Ioan LÄƒzÄƒrescu zum 65. Geburtstag gewidmet - Sava, Doris (Lexikos, 2018)
Romanian German in the 2016 edition of the German Variant Dictionary. Dedicated to Ioan LÄƒzÄƒrescu on his 65th Birthday. Towards the end of 2016, a fully revised, extended and updated second edition of the Variantenwörterbuch des Deutschen (German Variant Dictionary, GVD) was published, covering hitherto not lexicographically coded peculiarities of the German language in Romania, Namibia, and Mexico. In view of the changed normative thinking about standard language regionality, it is gratifying that the GVD undertakes to lexicographically document the entire variety spectrum beyond the boundaries of the closed German language area. Focussing on the written-language side of the standard varieties to which the inventory in the GVD is dedicated, the dictionary points out differences and thus peculiarities of the different varieties of the German language spoken in the quarter centres, in order to free them from their suspect assessment as non-standard. In the first edition of the GVD (2004), only the lexical variants of Standard German in countries and regions where German is the official and/or administrative language were coded. In view of this praiseworthy endeavor, it is important to question to what extent a convincing lexicographical treatment of the quarter centres, which had been unjustly neglected in the first edition, has been ensured. In the article, this will be exemplified on the basis of Romanian German. Raising awareness of typical manifestations in everyday use outside of the German official language area will promote the comparison of the quarter centres, and also contribute to the fact that this German is also perceived more intensively.